PENGGUNAAN MEDIA FLIP CHART DALAM MENINGKATKAN KEMAMPUAN BAHASA VERBAL ANAK AUTIS KELAS II DI SLB NEGERI 1 MAKASSAR - Nurul Safitri Andriani; Dwiyatmi Sulasminah; Bastiana Bastiana (-, 2024)
This study examines the improvement of the verbal language skills of autistic children using flip chart learning media in class II autistic children at SLB Negeri 1 Makassar. The formulation of the problem in this study is "Can the use of Flip Chart media improve the verbal language skills of autistic children?" The purpose of this study was to determine the increase in verbal language skills in class II autistic children. Data collection techniques are oral tests and documentation. The subject of this study was a class II autistic child with the initials DM. This study used an experimental method with a single subject (Single Subject Research/SSR) with an A-B-A research design. The results of this study indicate that 1) in baseline condition 1 (A1) the verbal language skills of autistic children before using flip chart media were in the very low category, 2) in the intervention conditions (B) the verbal language skills of autistic children when using flip chart media increased to the high category, 3) in baseline condition 2 (A2) there was an increase in the verbal language skills of autistic children after the application of flip chart media. The results of the study can be concluded that the use of flip chart media can improve the verbal language skills of class II autistic children.